2009
DOI: 10.1021/cg900437x
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Synthesis of Cu2O Crystals: Shape Evolution and Growth Mechanism

Abstract: An interesting shape evolution of Cu2O crystals, that is, from cubes, truncated octahedra, octahedra, and finally to nanospheres was first realized in high yield by reducing the copper−citrate complex solution with glucose. X-ray powder diffraction (XRD), field-emission scanning electron microscopy (FESEM), and high-resolution transmission electron microscopy (HRTEM) techniques were employed to characterize the samples. We elucidate the important parameters (including poly (vinyl pyrrolidone) (PVP) concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
119
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(133 citation statements)
references
References 82 publications
11
119
1
2
Order By: Relevance
“…For lanthanum hydroxide nanorods, the intensity ratio between the (100) and the (110) diffractions is 0.85, and between the (100) and the (101) diffractions is 1.19 which is significantly smaller than the conventional bulk intensity ratios (1.38 and 2.12, respectively) and lanthanum hydroxide nanoparticles ratios. This trend reveal that there is a direct relation between XRD patterns and shape of nanostructures because preferential growth of one face cause formation of specific shape and in the case of La(OH) 3 this preferential growth along the [100] direction forms 1D structure [35][36][37]. Figure 2 shows TEM image of lanthanum hydroxide nanorods, sample no.…”
Section: Resultsmentioning
confidence: 94%
“…For lanthanum hydroxide nanorods, the intensity ratio between the (100) and the (110) diffractions is 0.85, and between the (100) and the (101) diffractions is 1.19 which is significantly smaller than the conventional bulk intensity ratios (1.38 and 2.12, respectively) and lanthanum hydroxide nanoparticles ratios. This trend reveal that there is a direct relation between XRD patterns and shape of nanostructures because preferential growth of one face cause formation of specific shape and in the case of La(OH) 3 this preferential growth along the [100] direction forms 1D structure [35][36][37]. Figure 2 shows TEM image of lanthanum hydroxide nanorods, sample no.…”
Section: Resultsmentioning
confidence: 94%
“…In recent years, the morphology and size controlled synthesis of materials have attracted much attention due to their unique chemical and physical properties that are relevant to the shape and size [1][2][3][4][5][6]. Considerable efforts have been devoted to synthesize novel nano-and microstructured materials with various morphologies, such as low-dimensional structures (e.g., rods [7], wires [8,9], belts [10], tubes [11]) and hierarchical structures (e.g., branches [12], urchins [13], hollow spheres [14,15]), for their specific properties and corresponding potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…77-1584). The intensity ratio of the reflection peaks represents a well established approach used to discuss the crystal orientation against the standard powder XRD pattern [13,14]. Based on our detailed analysis, we observed that the intensity ratio between the (020) and (031) diffraction peaks gradually changed with different shapes obtained for samples in different concentrations of NaOH.…”
Section: Characterization Of the As-prepared Samplesmentioning
confidence: 77%